1993
DOI: 10.1016/s0007-1935(05)80210-6
|View full text |Cite
|
Sign up to set email alerts
|

Bovine coronavirus

Abstract: This review aims to summarize current data describing the characteristics of bovine coronavirus (BCV) and the three clinical syndromes with which this virus is associated. The first half of this paper consists of a general description of the virus, commencing with a brief outline of the methods used for in vitro growth. The structure of the virus is then described in more detail, with particular reference to the structure and functions of the four major viral proteins. This is followed by an outline of the uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
244
0
22

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(268 citation statements)
references
References 101 publications
2
244
0
22
Order By: Relevance
“…To our knowledge, this study is the first to survey the prevalence of WD and isolate WD BoCV in South Korea. The clinical manifestation in the cattle of the present herds was identical to that of WD reported elsewhere [5,6,8,10,12]. The consensus from those studies is that coronaviruses are commonly isolated from clinically typical cases of WD.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…To our knowledge, this study is the first to survey the prevalence of WD and isolate WD BoCV in South Korea. The clinical manifestation in the cattle of the present herds was identical to that of WD reported elsewhere [5,6,8,10,12]. The consensus from those studies is that coronaviruses are commonly isolated from clinically typical cases of WD.…”
supporting
confidence: 87%
“…Bovine coronavirus (BoCV), a member of the Coronaviridae family, causes severe newborn calves diarrhea (CD) and is associated with winter dysentery (WD) in adult cattle [5,10]. WD is characterized by a sudden onset of diarrhea that rapidly affects many adult cattle in a herd and has been reported in many parts of the world.…”
mentioning
confidence: 99%
“…BCoV is an enveloped virus with a single-stranded, positive-sense, non-segmented RNA genome of approximately 31 kb (Clark, 1993). A 4092 nt fragment of the BCoV genome encodes the large petal-shaped surface spike (S) protein.…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been demonstrated that BCoVs also circulate during the warmer seasons, but there are genetic differences between the warm-season and winterseason strains, which reflects on the ability of the virus to cause disease (Park et al, 2006). However, cattle are more efficiently infected in the winter, which increases the environmental contamination and justifies the high morbidity of WD during the cold months (Clark, 1993). Although tropical countries do not have the welldefined seasons of countries in the northern hemisphere, some counties in the southern region of Brazil have low temperatures and low UV light intensity during the winter.…”
Section: Introductionmentioning
confidence: 99%